Multiple Primary Lung Cancers With ALK Rearrangement: A Case Report and Literature Review - Huimin, Zhou; Xueting, Wang; Qi, Qi; Lingxin, Feng; Xue, Yang; Zhuang, Yu; Jing, Wang (Frontiers in Oncology, 2022)
Multiple primary lung cancers (MPLC) is that patients with lung cancer may present with two primaries at the same time (synchronous multiple primary lung cancer, SMPLC) or may develop a second, metachronous primary lung cancer after treatment of the initial lesion. Currently there are no unambiguous guidelines available for the diagnosis and treatment of MPLCs. Herein, we report a case of double primary lung cancers with ALK rearrangement. The patient was treated with chemotherapy, targeted therapy, radiotherapy. The patient is free of locally recurrent or distant disease at 2 years.